Witchlanders - Coakley, Lena, 1967- (Atheneum Books for Young Readers, 2011)
After the prediction of Ryder's mother, once a great prophet and powerful witch, comes true and their village is destroyed by a deadly assassin, Ryder embarks on a quest that takes him into the mountains in search of the destroyer.